Physical Activity, Brain Volume, and Dementia Risk: The Framingham Study - Tan, Zaldy S; Spartano, Nicole L; Beiser, Alexa S; DeCarli, Charles; Auerbach, Sanford H; Vasan, Ramachandran S; Seshadri, Sudha (The journals of gerontology. Series A, Biological sciences and medical sciences, 2017)
Several longitudinal studies found an inverse relationship between levels of physical activity and cognitive decline, dementia, and/or Alzheimer's disease (AD), but results have been inconsistent. We followed an older, community-based cohort for over a decade to examine the association of physical activity with the risk of incident dementia and subclinical brain MRI markers of dementia. The physical activity index (PAI) was assessed in the Framingham Study Original and Offspring cohorts, aged 60 years or older. We examined the association between PAI and risk of incident all-cause dementia and AD in participants of both cohorts who were cognitively intact and had available PAI (n = 3,714; 54% women; mean age = 70±7 years). We additionally examined the association between PAI and brain MRI in the Offspring cohort (n = 1,987). Over a decade of follow-up, 236 participants developed dementia (188 AD). Participants in the lowest quintile of PAI had an increased risk of incident dementia compared with those in higher quintiles (hazard ratio [HR] = 1.50, 95% confidence interval [CI] = 1.04-1.97, p = .028) in a multivariable-adjusted model. Secondary analysis revealed that this relation was limited to participants who were apolipoprotein (APO)E ε4 allele noncarriers (HR = 1.58, 95% CI = 1.08-2.32; p = .018) and strongest in participants aged 75 years or older. PAI was also linearly related to total brain and hippocampal volumes (β ± SE = 0.24±0.06; p < .01 and 0.004±0.001; p = .003, respectively). Low physical activity is associated with a higher risk for dementia in older individuals, suggesting that a reduced risk of dementia and higher brain volumes may be additional health benefits of maintaining physical activity into old age.